New Indicators for Tracking Growth in Real Time - Matheson, Troy (IMF Working Papers; Working Paper ;, 2011)
We develop monthly indicators for tracking growth in 32 advanced and emerging-market economies. We test the historical performance of our indicators and find that they do a good job at describing the business cycle. In a recursive out-of-sample forecasting exercise, we find that the indicators generally produce good GDP growth forecasts relative to a range of time series models.